2021
DOI: 10.3390/coatings11080998
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of MIG Welding and Preheat Parameters for 6061-T6 Al Alloy T-Joints Using Artificial Neural Networks Based on FEM

Abstract: To control the welding residual stress and deformation of metal inert gas (MIG) welding, the influence of welding process parameters and preheat parameters (welding speed, heat input, preheat temperature, and preheat area) is discussed, and a prediction model is established to select the optimal combination of process parameters. Thermomechanical numerical analysis was performed to obtain the residual welding deformation and stress according to a 100 × 150 × 50 × 4 mm aluminum alloy 6061-T6 T-joint. Owing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Q is the AM deposition energy. Table 1 shows the heat source parameters used in the study, which are based on the previous reference [35]. A thermomechanical constitutive equation is employed in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Q is the AM deposition energy. Table 1 shows the heat source parameters used in the study, which are based on the previous reference [35]. A thermomechanical constitutive equation is employed in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the development of corresponding control technology based on numerical simulation becomes imperative. Numerical simulations enable the effective prediction of the distribution of the welding temperature field and welding stress field [ 3 , 4 , 5 ], facilitating the optimization of welding process parameters [ 6 , 7 , 8 , 9 , 10 ]. This optimization enhances welding quality, reduces production costs, and enhances production efficiency in the welding process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the welding sequence had a substantial effect on the plate deformation and longitudinal stress distribution induced by welding [ 21 ], according to Chen et al Fallahi et al [ 22 ] discovered that preheating and proper welding sequences were effective in reducing residual stresses during welding. Shao et al [ 23 ] found that the preheating temperature and welding speed had the greatest impact on the welding stress and deformation of aluminum alloy T-joints, followed by the preheating area. Peric et al [ 24 ] studied the effects of different preheating temperatures and inter-pass times on the residual stress and deformation of the welded structure.…”
Section: Introductionmentioning
confidence: 99%